IPTEK BAGI WILAYAH KECAMATAN LEBONG TENGAH KABUPATEN LEBONG - Reswita Reswita; Satria Putra Utama; Kurnia Herlina Dewi; Yulfiperius Yulfiperius (DHARMA RAFLESIA, 2018)
Central Lebong Sub District is one district that has significant potential in the district Lebong. The biggest potential is in agriculture, including food crops, plantations and fisheries. Although it has great potential, but there are still many problems faced by the region administration in the District Lebong Lebong Central. The programs that have been implemented as a solution for dealing with problems in the target areas IBW III is 1) Procurement of equipment to support the manufacture of palm sugar ants and entrepreneurial activity, 2) Increased production of palm sugar ants, 3) Trained making of coffee powder, 4)  trained making palm civet coffee, 5) trained making of ginger coffee, 6) Increased production of coffee Brown Sugar, 7) Improved the economic of women through entrepreneurship training, 8) Promotional products through direct sales and exhibition, 9) Home gardens for garden plants, inland fisheries, and livestock in an integrated way, 10)  Environmental health education and the availability of clean water, 11) Trained the manufacture of fish feed for the farmer groups, 12) Provided assistance toilet facilities. Keywords: palm sugar, products diversification, refined palm sugar, IbW palm coffee